2016
DOI: 10.1038/srep29835
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase is crucial for maintaining pupal tanning and immunity in Anopheles sinensis

Abstract: Tyrosine hydroxylase (TH), the initial enzyme in the melanin pathway, catalyzes tyrosine conversion into Dopa. Although expression and regulation of TH have been shown to affect cuticle pigmentation in insects, no direct functional studies to date have focused on the specific physiological processes involving the enzyme during mosquito development. In the current study, silencing of AsTH during the time period of continuous high expression in Anopheles sinensis pupae led to significant impairment of cuticle ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…According to our observations of pupae phenotype in different developmental stages, the cuticle tanning pattern is the same in the male and female pupae [12]. The cuticle colour of the female pupae is a little transparent with a slight yellowish tint within 24 h after pupation (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…According to our observations of pupae phenotype in different developmental stages, the cuticle tanning pattern is the same in the male and female pupae [12]. The cuticle colour of the female pupae is a little transparent with a slight yellowish tint within 24 h after pupation (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…2b). Interestingly, a retarded expression pattern of AsLac2 was observed when compared with the upstream, rate-limited gene AsTH [12], indicating that the catalytic function of AsLac2 occurred after the accumulation of catecholamine. Furthermore, we found that the expression intensity of AsLac2 in the pupae (from the early-middle to the last stage) was significantly stronger than that in the adults (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations